2021
DOI: 10.1093/plphys/kiab390
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics approach reveals a role of translational machinery in shaping maize kernel amino acid composition

Abstract: Maize (Zea mays) seeds are a good source of protein, despite being deficient in several essential amino acids. However, eliminating the highly abundant but poorly balanced seed storage proteins has revealed that the regulation of seed amino acids is complex and does not rely on only a handful of proteins. In this study, we used two complementary omics-based approaches to shed light on the genes and biological processes that underlie the regulation of seed amino acid composition. We first conducted a genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…This study identified proteins that make up the composition of kernel protein bodies in maize. A second study, Shrestha et al. (2022) , performed GWAS on several kernel protein boundamino acid phenotypes in a diverse maize population ( Shrestha et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study identified proteins that make up the composition of kernel protein bodies in maize. A second study, Shrestha et al. (2022) , performed GWAS on several kernel protein boundamino acid phenotypes in a diverse maize population ( Shrestha et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data were collected from 3,873 leaf mass features [37], 116,381 RNA expression values from seven tissues [38], and 343 field traits. Field traits included flowering time [3,69], plant architecture [21,46,[70][71][72][73][74][75], disease and insect resistance [76][77][78][79][80][81][82][83], and kernel composition [84][85][86][87][88][89][90]. Many of these traits are replicated across environments, so a single representative version of that trait was kept.…”
Section: Collection Of a Wide Range Of Phenotypes In Nam And Gapmentioning
confidence: 99%
“…These population-trait categories were: 1) NAM field, 2) GAP field, 3) GAP mass features, and 4) GAP expression traits. Some traits within GAP field traits included kernel carotenoids and metabolites [84,86,[88][89][90], which could be classified into GAP mass features type because they are also molecular phenotypes. However, only the metabolites measured within a single study were classified as GAP mass features [37].…”
Section: Collection Of a Wide Range Of Phenotypes In Nam And Gapmentioning
confidence: 99%
“…Targeted translation of mRNAs based on altered ribosomal structures is referred to as ribosome specialization ( Genuth and Barna, 2018 ; Martinez-Seidel et al, 2020 ; Slavov et al, 2015 ). Functional specialization of ribosomes entails translational events that drive a response to an external ( Lambers, 2022 ; Berková et al, 2020 ; Moin et al, 2021 ; Appels et al, 2021 ) or a developmental ( Norris et al, 2021 ; Shrestha et al, 2022 ; Xiong et al, 2021 ) cue, for example, the preferred translation of specific groups of proteins that facilitate acclimation to low temperatures. These concepts suggest that the previously observed abundance changes of the translational machinery in cold-acclimating root tips of barley seedlings ( Martinez-Seidel et al, 2021c ) may indicate the production of ribosomes tuned to cold-specialized translation.…”
Section: Introductionmentioning
confidence: 99%